Application of AC plasma display panels to radiation detectors. Issue 2 (22nd January 2016) - Murai, Ryuichi; Murata, Mitsuhiro; Shintani, Yoichi
Abstract: Radiation detector proposals that use plasma display panels are rare. In this work, we confirmed a radiation detector that uses plasma display panels that are focused on the breakdown voltage shift in the ramp waveform. We adapted the cell structures, gas contents, and waveforms of plasma display panels (AC‐PDPs) for radiation detectors. Hard X‐rays and gamma rays induce electron emission into the discharge gas, resulting in generating electrons, electron multiplication, and charge accumulation on dielectrics. The radiation dose rate of hard X‐rays and gamma rays (Cs137) is measured as a breakdown voltage shift between anodes and cathodes. For gamma rays, the detection sensitivity in this experiment is not as high as in the case of hard X‐rays, but the detector can locate gamma rays. These results suggest that adapted AC‐PDPs can detect both hard X‐rays and gamma rays and can be used in a large two‐dimensional radiation detector. Abstract : We confirmed a radiation detector that uses plasma display panels that are focused on the breakdown voltage shift in the ramp waveform. We adapted the cell structures, gas contents, and waveforms of plasma display panels (AC‐PDPs). Hard X‐rays and gamma rays induce electron emission into the discharge gas, resulting in generating electrons, electron multiplication, and charge accumulation on dielectrics. The radiation dose rate of hard X‐rays and gamma rays (Cs137) is measured as a breakdown voltage shift between anodes and cathodes.